(untitled) (Journal of the College of Basic Education, 2022)
And the retention of second-grade middle school students in mathematics.The research sample consisted of (40) female students in Al-Wafa Secondary School for Girls of the General Directorate of Education of Baghdad / Al-Rusafa II, who were chosen randomly, and each division consisted of (20) students, where division (A) represented the experimental group that was studied using the survey strategy, and division (B) represented The control group, which was taught using the usual method of teaching, the researcher used the experimental design (the experimental group and the control group) and the partial control.